ANALISIS IMPOR GULA INDONESIA TAHUN 2000-2019 - Rina Dwipurwanti; Hadi Sasana (Melati Institute, 2022)
Sugar is one of the main staple foods after rice. Sugar consumption in Indonesia is always increasing every year so that the government continues to import sugar. This study aims to analyze the factors that influence sugar imports in Indonesia. The data used are secondary data from time series 2000-2019. The data in this study were obtained from BPS. The variables used in this study were sugar imports, production, domestic sugar prices, and exchange rates. The econometric analysis model used in this study is the Error Correction Model (ECM). The results of this study concluded that sugar production and sugar consumption had no effect on sugar imports, the domestic price of sugar and the rupiah exchange rate against the USD had an effect on sugar imports in Indonesia in the long run.